Kajian Gerak dalam Pertunjukan Tari Barapan Kebo di Sanggar Sareng Nyer Kabupaten Sumbawa Barat - Saputra, Herdyon; Yuliatin, Riyana Rizki; Kailani, Ashwan (Universitas Hamzanwadi, 2020)
This study aims to describe the form of performances and movement of Barapan Kebo Dance in Sanggar Sareng Nyer, Sumbawa Barat Regency. This study uses the theory of performing arts Y.Sumandiyo Hadi (2018: 5) that the performing arts are always associated with aspects of time, space, and the player, the theory of motion dance Robby Hidajat (2018: 81) that the motion of the dance is a process of moving from one posture to the attitude of the other. The study was conducted at Sanggar Sareng Nyer, Sumbawa Barat Regency. This study was a qualitative method. The Primary data sources were Barapan Kebo dance performances and secondary data sources in the form of documents, photos, recordings, videos and others that can enrich primary data. The techniques of data collection were 1) observation, 2) interviews, 3) documentation. The data analysis techniques were used by 1) data reduction, 2) data presentation, and 3) data inference. Meanwhile, to check the validity of the data was done by using the data triangulation technique. The results showed that the form of seven stages of the Barapan Kebo dance performance and dance movements that used several typical Sumbawa Barat movements, the movements in the Barapan Kebo Dance include ngomek ngompeng, bagerik, barue’, marenjang, kaliung luntar, ngijik, bejampi, basalunte, and bakeja. There was a division of meaningful and pure movements, meaningful movements including bejampi, basalunte, ngomek ngompeng, and ngijik. Meanwhile, pure motion includes marenjang, kaliung luntar, bagerik, barue', and bakeja.